1976
DOI: 10.1007/bf01972217
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in intro macrophage activation by systemic adjuvants

Abstract: Six systemic adjuvants of immunity were tested for their ability to induce macrophage activation. Four of them: living BCG, hydrosoluble extracts from BCG (HIU II) and from M.smegmatis (IPM), and lipopolysaccharide from E.coli (LPS), when administered to normal mice render macrophages non-specifically cytotoxic for tumor cells in vitro. The intensity of this phenomenon varied according to the route and time of adjuvant administration. In contrast, lentinan extracted from Lentinus edodes, and levamisole which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…In addition, LPS-activated macrophages and dendritic cells were studied. LPS was chosen as an activating factor because it is known as an activator of dendritic cells, since it induced maturation and migration (21,46), and LPS effectively activates macrophages and induces tumoricidal activity (5,14). When cells were activated with LPS, no expression of other sst subtypes could be detected, suggesting a selective role for sst 2 in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LPS-activated macrophages and dendritic cells were studied. LPS was chosen as an activating factor because it is known as an activator of dendritic cells, since it induced maturation and migration (21,46), and LPS effectively activates macrophages and induces tumoricidal activity (5,14). When cells were activated with LPS, no expression of other sst subtypes could be detected, suggesting a selective role for sst 2 in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sulphated derivative of lentinan was proven to be a powerful adjuvant in chickens immunized with Newcastle disease vaccine with an increased serum antibody titre and proliferation of lymphocytes [17]. Moreover, lentinan suppresses tumouricidal activity of macrophages non-specifically unlike other adjuvants such as lipopolysaccharide (LPS) [49].…”
Section: Natural Polymersmentioning
confidence: 99%
“…In the presence of an injury in which the RES participates in protecting the host, the RES undergoes several changes characterized by early decreased activity followed by 48 h with a period of enhanced phagocytic activity [8], When lipopolysaccharide is administered intraperitoneally, a state of RES hyperphago cytosis occurs by 24 h [10,11]. The enhanced RES enables the host to more effectively cope with injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pre vious studies have demonstrated that this regimen is effective in stimulating RES phagocytic function as determined by the rate of clearance of injected carbon [10,11]. The animals were feeding well and were indis tinguishable from the controls at the time of the uptake study.…”
Section: Reticuloendothelial Stimulationmentioning
confidence: 99%